Determinants of the repetitive-CMAP occurrence and therapy efficacy in slow-channel myasthenia. (17th November 2020) - Di, Li; Chen, Hai; Lu, Yan; Selcen, Duygu; Engel, Andrew G.; Da, Yuwei; Shen, Xin-Ming
Abstract : Objective: To find determinants of the occurrence of repetitive compound muscle action potential (R-CMAP) and to assess the efficacy of channel blocker therapy in slow-channel congenital myasthenic syndrome (SCCMS). Methods: Neurologic examination, EMG study, laboratory test, muscle biopsy, and next-generation and Sanger sequencing; literature review of reported patients with SCCMS, including EMG, kinetics of mutant acetylcholine receptors (AChRs), and response to therapy; and simulation of the decay phase of endplate potential (EPP) were performed. Results: Three newly characterized and 57 reported patients with SCCMS with mutations of AChR subunits were included. In patients with R-CMAP, the length of channel opening bursts of mutant AChR was increased 8.68 ± 2.82 (mean ± SD)-fold compared to wild-type; in patients without R-CMAP, the length was increased 3.84 ± 0.65-fold (95% confidence interval 3.18–6.50, p = 0.000014). The EPP amplitude after refractory period of action potential in muscle fiber is above the threshold in patients with R-CMAP but below the threshold in patients without R-CMAP. In patients with good results from channel blocker therapy, treatment was initiated 11.60 ± 5.17 years after onset of symptoms; in patients with no to moderate benefit from channel blocker therapy, treatment was initiated 30.70 ± 12.72 years after onset (95% confidence interval −28.57 to −9.63, p = 0.00089). Conclusions: In SCCMS, the R-CMAP occurrence is related to the extent of prolongation of the opening episodes of mutant AChR channel. Channel blocker treatment is more effective the sooner it is started after the onset of symptoms. Classification of evidence: This study provides Class IV evidence that channel blocker therapy in patients with SCCMS improves symptoms.